2014
DOI: 10.3402/jom.v6.23419
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus gordonii glucosyltransferase promotes biofilm interactions with Candida albicans

Abstract: BackgroundCandida albicans co-aggregates with Streptococcus gordonii to form biofilms and their interactions in mucosal biofilms may lead to pathogenic synergy. Although the functions of glucosyltransferases (Gtf) of Mutans streptococci have been well characterized, the biological roles of these enzymes in commensal oral streptococci, such as S. gordonii, in oral biofilm communities are less clear.ObjectiveThe objective of this work was to explore the role of GtfG, the single Gtf enzyme of S. gordonii, in biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…A similar mechanism may also enhance C. albicans and S. gordonii biofilm formation in vitro (73). Altogether, we demonstrate the importance of Gtfs in mediating the cooperativity between C. albicans and S. mutans.…”
Section: Discussionsupporting
confidence: 63%
“…A similar mechanism may also enhance C. albicans and S. gordonii biofilm formation in vitro (73). Altogether, we demonstrate the importance of Gtfs in mediating the cooperativity between C. albicans and S. mutans.…”
Section: Discussionsupporting
confidence: 63%
“…sucrose) or trisaccharides and transfer the appropriate monosaccharide to form a-linked polymers. Since we utilized a monosaccharide as carbon and energy source in our studies, no glucans would be produced (Ricker et al, 2014). It has been suggested that release of eDNA by streptococcal cells during early stages of biofilm formation could involve a specialized active release mechanism (Xu & Kreth, 2013) via lysis-independent membrane vesicles (Liao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A Gtf-negative mutant of S. gordonii showed diminished persistence on the teeth of sucrose fed rats, although initial colonization was not affected (79). In addition, deletion of the single gtf gene of S. gordonii , gtfG , impacted its ability to form mixed biofilms with Candida albicans (80). Streptococcus sanguinis also produces water soluble glucans from sucrose through a Gtf enzyme called GtfP.…”
Section: Mechanisms Of Colonizationmentioning
confidence: 99%